Kan schackrutehuggning mildra konflikten mellan skogsbruk och renskötsel? - Gunnarsson, Ylva (2022)
The forest is considered a national asset in which many values must coexist. As a consequence, conflicts arise between different interests. Since the 1950s, clear-cutting has been the most common way of forest management in Sweden. Reindeer husbandry is negatively affected when the forest is clear-cut and is therefore in need of the forest to be managed in other ways than today. At the same time, the government wants to increase the proportion of continuous cover forestry. Chequered-Gap-Shelterwood-System is a forestry method that is regarded as a continuous cover forestry. Using a grid pattern, half the area is harvested while the rest is left to be harvested at a later time. This method is currently only available at the experimental level but is said to combine benefits from both clear-cutting and continuous cover forestry. The overall purpose of the study is to map whether Chequered-Gap-Shelterwood-System can reduce the conflict between forestry and reindeer husbandry. Through semi-structured interviews with three reindeer herders and three employees at forest companies, two main issues were studied. One was about their attitude towards the method and the other about how they thought it would be best applied. An interesting result is the perception that the method can benefit the snow conditions and the treelichen's dispersibility in relation to clear felling. The conclusion is that the attitude towards Chequered-Gap-Shelterwood-System is surprisingly positive and the analyse is that the method has the potential to reduce the conflict between the two industries. Application of the method can be used in areas that are important for reindeer husbandry and as a substitute for clear-cutting. The time between the harvests must be at least long enough for the regeneration in the openings to have time to grow above the snow cover. Skogen är en nationell tillgång och i den ska många värden rymmas, som en konsekvens uppstår konflikter mellan olika intressen. Sedan 1950-talet har trakthyggesbruk varit det vanligaste ...